New species of Victoriopisa Karaman & Barnard, 1979 (Crustacea: Amphipoda: Eriopisidae) from Vembanad backwaters, Southwest coast of India - Joseph, Philomina; Nandan, S. Bijoy; Jayachandran, P.r. (Zootaxa, 2018)
The new species is the third of genus Victoriopisa from Indian waters.The species is described from the Valanthakad mangrove area of Vembanad backwater. Victoriopisa cusatensis sp. nov differs from other species of Victoriopisa by presenting: (1) a characteristic projection at dorsolateral margin of peduncle article 2 of antenna 1in male while smooth in female; (2) broad, triangular lateral cephalic lobe; (3) posteroventral tooth in epimeral plates; (4) presence of lateral and subapical spines in telson (5) smooth palm of gnathopod 2 without any excavations.